Cost-effectiveness of meningococcal vaccination of Norwegian teenagers with a quadrivalent ACWY conjugate vaccine. Issue 8 (3rd August 2021) - Watle, Sara Viksmoen; Næss, Lisbeth Meyer; Tunheim, Gro; Caugant, Dominique A.; Wisløff, Torbjørn
ABSTRACT: In Norway, the incidence of invasive meningococcal disease (IMD) is higher among 16–19-year-olds than in the general population. Most IMD cases among teenagers are caused by serogroup Y. Since 2011, one dose of meningococcal ACWY conjugate vaccine (MCV4) has been recommended for teenagers with out-of-pocket payment. The teenagers are usually vaccinated through the school health service at age 18. This study aimed to estimate costs and health gains of introducing MCV4 to Norwegian teenagers through the national immunization program (NIP). A Markov model was used to analyze the cost-effectiveness of universal MCV4 vaccination of either 15-year-olds or 18-years-olds. Occurrences of IMD were simulated from 15 until 23 years of age. Costs were estimated from a healthcare perspective. Sensitivity analyses evaluated the impact of vaccine price, vaccination uptake, IMD incidence and discount rate. Compared to today's practice of vaccinating 18-year-olds with out-of-pocket payment, introducing MCV4 to 15-year-olds in a NIP-setting, with 90% vaccine uptake and 50% rebate on vaccine price, prevented 3.2 hospitalizations, 0.20 sequelae and 0.47 deaths among 15–23-year-olds, annually. Total costs were reduced by €30, 000 and 9.7 quality-adjusted life-years (QALYs) were gained per birth cohort. The probability of cost-effectiveness was 99.0%, assuming a willingness-to-pay threshold of €86, 000/QALY for severe diseases in Norway. Cost-effectiveness was highly dependent on vaccine price. Vaccination of 18-year-olds in a NIP-setting was also cost-effective, but less than NIP-vaccination of 15-year-olds. Introduction of MCV4 to the 15-year-olds in the Norwegian NIP is likely to be cost-effective given a rebate on the vaccine price.